Criteria for Coordination in Slovenian Multiclause Sentences - Gabrovšek, Dejan (Slavistica Vilnensis, 2024)
The article presents and explains the criteria for coordination in the Slovenian compound sentence. The most important criteria are the same status of both clauses, i.e. symmetry, interchangeability in the order of clauses, the fact that the non-initial clause expresses new information, the possibility of adding clauses, the temporal iconicity principle, the fact that backwards anaphora is not possible, and the coordinate structure constraint. Slovenian examples from the corpus are used to demonstrate almost every criterion. At the end of the article, it is pointed out that not all the criteria can be applied to all the constructions considered coordinate, which is to be expected given the complex nature of a language, so it is better to say that there are different degrees of dependency rather than just subordination (complex sentences) and coordination (compound sentences): the more criteria for coordination a particular construction fulfils, the more coordinate it is, and the fewer criteria for coordination a particular construction fulfils, the less coordinate it is and thus closer to the subordinate pole. Some of the criteria for coordination shown here also apply to structures that are normally considered subordinate. Conversely, some of the criteria for subordination also apply to certain structures that are normally considered coordinate. There is no clear line between coordination and subordination, but rather a continuous gradient from the most coordinate to the most subordinate.